Pengaruh Kualitas Produk, Labelisasi Halal dan Variasi Produk Terhadap Keputusan Pembelian Lipstik Wardah (Studi pada Masyarakat Kecamatan Tuah Madani Kota Pekanbaru) - Reny Mirnayana; Ainun Mardiah (Al-Manar Journal of Economic and Social Studies, 2024)
The purpose of this study was to determine whether product quality, halal labeling and product variations affect the purchase decision of Wardah Brand Lipstick in the Tuah Madani District Community, Pekanbaru City. The sample in this study amounted to 100 respondents selected using Purposive Sampling. The data analysis method used is the quantitative description method. The results showed that partially Product Quality and Product Variety has a significant effect on the Purchase Decision of Wardah Brand Lipstick in the Community of Tuah Madani Subdistrict, Pekanbaru City, and then Halal Labeling variable  has no significant effect on the Purchase Decision of Wardah Brand Lipstick in the Community of Tuah Madani Subdistrict, Pekanbaru City. While simultaneously Product Quality, Halal Labeling and Product Variety have an influence on the Wardah Brand Lipstick Purchasing Decision in the Community of Tuah Madani District, Pekanbaru City. The results of this study explain that Product Quality, Halal Labeling and Product Variety as a whole have an influence of 67.9% on the Purchasing Decision variable.